Monetary policy and global banking - Falk Bräuning; Victoria Ivashina (Federal Reserve Bank of Boston, 2016)
Global banks use their global balance sheets to respond to local monetary policy. However, sources and uses of funds are often denominated in different currencies. This leads to a foreign exchange (FX) exposure that banks need to hedge. If cross-currency flows are large, the hedging cost increases, diminishing the return on lending in foreign currency. We show that, in response to domestic monetary policy easing, global banks increase their foreign reserves in currency areas with the highest interest rate, while decreasing lending in these markets. We also find an increase in FX hedging activity and its rising cost, as manifested in violations of covered interest rate parity.
Keywords: E44; E52; F36; G15; G21; G28; 330; global banks; monetary policy transmission; cross-border lending